PERAN GURU MENGATASI KECEMASAN BERBICARA SISWA PADA PEMBELAJARAN BAHASA INDONESIA KELAS V SDN BADANDAN 1 - Nazar Ahmad; Akhmad Humaidi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the speaking anxiety experienced by students during Indonesian language learning, particularly when expressing opinions, answering questions, or speaking in front of the class. This condition affects students' confidence, speaking fluency, and willingness to communicate. The study aimed to identify the forms of students' speaking anxiety, analyze the roles and strategies of teachers in overcoming speaking anxiety, and identify the obstacles encountered by teachers in addressing students' speaking anxiety. This research employed a descriptive qualitative approach. The participants consisted of one fifth-grade teacher and six fifth-grade students at SDN Badandan 1. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. Data validity was ensured through source, technique, and time triangulation. The findings revealed that students experienced two forms of speaking anxiety, namely trait anxiety and state anxiety, with state anxiety being the more dominant form. Teachers played important roles by creating a supportive classroom atmosphere, providing opportunities for students to speak, offering motivation and constructive feedback, and establishing positive relationships with students. The strategies implemented included personal approaches, group activities, gradual speaking practice, and art-based activities such as singing and drawing. The main obstacles originated from students' internal factors, including low self-confidence, shyness, fear of making mistakes, fear of negative evaluation, difficulty expressing ideas, and limited vocabulary.